Molecular Diagnostic Tools for Treponema pallidum - Setyarini, Wahyu; Wiqoyah, Nurul; Muhammad Ansori (Institute of Topical Disease Universitas Airlangga, 2023)
Syphilis, a common sexually transmitted disease, is caused by Treponema pallidum subsp. pallidum. Owing to the chameleonic behavior of syphilis, ocular involvement still presents a therapeutic problem. Direct detection of Treponema pallidum in the vitreous offers a potential diagnostic method because serodiagnosis has considerable limitations. The worldwide identification of T. pallidum substypes has occurred since the advent of molecular typing approaches. The purpose of this article is to provide more information on the development of a molecular approach for Treponema pallidum detection. A body of literature was gathered using automated database searches in Google Scholar, PubMed, and ScienceDirect. Although prior studies have focused on other genes, such as polA, 16S RNA, and the whole genome, there are still some that use the study of the arp and T. pallidum repeat (tpr) genes to subtype. Whole blood, vaginal ulcers, skin biopsies, and other samples can be used in molecular methods. Comparing quantitative reverse trascription-polymerase chain reaction (qRT-PCR) to traditional methods, such as reverse transcription-polymerase chain reaction (RT-PCR), enzyme-linked immunosorbent assay (ELISA), indirect fluorescent antibody (IFA) assay, and virus isolation, qRT-PCR has the advantage of being faster and more sensitive. Quick molecular methods, particularly polymerase chain reaction (PCR) results, will enable early detection of primary, secondary, and latent syphilis, which will lead to prompt treatment and prevention of disease progression as well as a reduction in the amount of time that the patient's sexual partners are exposed to the illness.